Silicon carbon material as well as preparation method and application thereof

By depositing hollow silicon nanotubes on the porous carbon framework and installing doped layers, the problem of high volume expansion rate of silicon-based materials during the lithium embedding process is solved, and the effect of reducing lithium embedding expansion and improving battery circulation performance is achieved.

CN119601628APending Publication Date: 2025-03-11REPT BATTERO ENERGY CO LTD +1
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411764561.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing silicon-based materials have a high volume expansion rate during lithium embedding, resulting in material cracking and SEI film rupture, affecting interface stability, and continuously consume electrolyte during the cycle, resulting in a decrease in battery capacity retention rate.

Method used

Using porous carbon as the framework, the silicon deposited in its pores forms hollow silicon nanotubes. By adjusting the pore size distribution of porous carbon and the deposition method of silicon, the overall lithium embedded expansion is reduced, and doped layers are provided on the outer surface of the porous carbon and the inner wall of the hollow silicon nanotube to improve the stability of the SEI film.

Benefits of technology

It effectively reduces the lithium embedded in silicon carbon material, reduces the material breakage, improves the battery's circulation performance and capacity retention rate, and avoids the battery's capacity dip in the later stage of cycle.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601628A_ABST
    Figure CN119601628A_ABST
Patent Text Reader

Abstract

The invention discloses a silicon-carbon material and a preparation method and application thereof, belongs to the technical field of negative electrode materials, and overcomes the defect of high volume expansion rate of a silicon-based material in the prior art. The silicon-carbon material provided by the invention comprises porous carbon and silicon deposited in porous carbon channels; the porous carbon comprises mesopores and macropores, the pore diameter of the mesopores is greater than 10nm and less than or equal to 50nm, and the pore diameter of the macropores is greater than 50nm and less than or equal to 100nm; based on the total volume of the pores in the porous carbon, the volume fraction of the mesopores is 50%-75%, and the volume fraction of the macropores is 10%-20%; and the silicon deposited in the mesopores and the macropores is a hollow silicon nanotube. Silicon in the silicon-carbon material mainly exists in the form of hollow silicon nanotubes, and during lithium intercalation expansion, since expansion spaces are reserved in the hollow nanotubes, the lithium intercalation expansion of the whole silicon-carbon material is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of negative electrode materials, and in particular relates to a silicon-carbon material and a preparation method and application thereof. Background Art

[0002] Silicon-based materials have the advantages of high theoretical specific capacity (4200mAh / g), abundant reserves and low price, and are the first choice for the next generation of high-gram capacity negative electrode materials for secondary batteries. However, the volume expansion rate of silicon-based materials is high (greater than 300%) during the lithium insertion process, which will cause the silicon material itself to crack and the SEI film on the surface of the particles to rupture, affecting the interface stability between the silicon-based particles and the electrolyte; and in the subsequent cycle process, the formation of a new SEI film at the rupture site requires the re-consumption of the key film-forming components in the electrolyte (lithium salts, solvents, film-forming additives, etc.), and the repeated process of rupture and regeneration will lead to their continuous consumption, and even in the later stage of the cycle, the content will be lower than the normal level or even exhausted, and the battery capacity retention rate will drop.

[0003] Therefore, reserving a certain space inside the material for the expansion of silicon is one of the ideas for the development of silicon-based materials. The document Yolk-shell Si / C composites with multiple Si nanoparticles encapsulated into double carbon shells as lithium-ion battery anodes introduces a silicon-carbon material with a yolk-shell structure. The Si particles are first oxidized to obtain Si particles with SiO2 coated on the surface, followed by surface carbon coating and HF etching of SiO2 twice, and finally the yolk-shell structure is obtained. In the structure, the Si nanoparticles are the core, the carbon material is the shell, and the etched SiO2 area is the cavity area reserved for expansion. The use of a large amount of etchant in the preparation process of silicon-carbon materials with a yolk-shell structure will cause environmental pollution, and the size of the cavity is usually difficult to fully meet the expansion requirements of the Si particles.

[0004] Therefore, it is necessary to develop new low-expansion silicon-based materials. Summary of the invention

[0005] Therefore, the technical problem to be solved by the present invention is to overcome the defect of high volume expansion rate of silicon-based materials in the prior art, thereby providing a silicon-carbon material and a preparation method and application thereof.

[0006] To this end, the present invention provides the following technical solutions.

[0007] In a first aspect, the present invention provides a silicon-carbon material, comprising porous carbon and silicon deposited in the pores of the porous carbon;

[0008] The porous carbon includes mesopores and macropores, with the pore size of the mesopores being 10nm<≤50nm, and the pore size of the macropores being 50nm<≤100nm;

[0009] Based on the total volume of the pores on the porous carbon, the volume fraction of the mesopores is 50% to 75%, and the volume fraction of the macropores is 10% to 20%;

[0010] The silicon deposited in the mesopores and macropores is hollow silicon nanotubes.

[0011] Silicon is also deposited on the outer surface of the porous carbon.

[0012] In a possible implementation, the wall thickness of the hollow silicon nanotube is 0.6 to 5 nm, preferably 0.6 to 3 nm, and more preferably 1.8 to 2.4 nm.

[0013] In a possible implementation, based on the total volume of pores on the porous carbon, the volume fraction of the mesopores is 58% to 70%.

[0014] In a possible implementation, the porous carbon further comprises small pores with a pore diameter of ≤10 nm, and based on the total volume of pores on the porous carbon, the volume fraction of the small pores is ≤40%;

[0015] The silicon deposited in the small holes is solid silicon nanowires and / or hollow silicon nanotubes.

[0016] The diameters of both solid silicon nanowires and hollow silicon nanotubes are comparable to the pore size of the pores in which they are deposited.

[0017] In a possible implementation, the silicon-carbon material further includes a coating layer disposed on the outer surface of the porous carbon and / or the inner wall of the hollow silicon nanotube;

[0018] Optionally, the coating layer is selected from at least one of a carbon coating layer, a polymer coating layer, a metal oxide coating layer and an organic-inorganic composite coating layer.

[0019] The “inner wall” refers to the side of the hollow silicon nanotube away from the porous carbon, e.g. Figure 1 As shown, the coating layer is arranged on the outer surface of the porous carbon and / or the inner wall of the hollow silicon nanotube.

[0020] In a possible implementation manner, a doping layer is provided on the outer surface of the porous carbon and / or the inner wall of the hollow silicon nanotube;

[0021] Optionally, the doping layer composition includes S x , wherein x is selected from at least one of 2, 4, 6, and 8;

[0022] Optionally, the doping layer is disposed between the porous carbon and the coating layer, and / or the doping layer is disposed between the inner wall of the hollow silicon nanotube and the coating layer;

[0023] Optionally, the mass of the doping layer accounts for 0.1% to 5%, preferably 0.5% to 2%, of the sum of the mass of the porous carbon, silicon and the doping layer.

[0024] In a possible implementation, the specific surface area of ​​the silicon-carbon material is 0.7 to 10 m 2 / g, optional 1~2m 2 / g.

[0025] In a possible embodiment, the particle size Dv50 of the silicon-carbon material is 8 to 10 μm. 2 / g.

[0026] In a second aspect, the present invention provides a method for preparing a silicon-carbon material, comprising the following steps:

[0027] S1. Obtaining porous carbon: pyrolyzing a carbon source precursor under a protective gas A, crushing and classifying the carbon powder, mixing the carbon powder with an activator, and then heating the mixture to activate and form pores, thereby obtaining the porous carbon;

[0028] The activation pore-forming time is 5 to 24 hours;

[0029] S2, depositing silicon in the pores of porous carbon;

[0030] S3. Prepare a coating layer.

[0031] In a possible implementation manner, S1 satisfies at least one of the following conditions:

[0032] (1) The pyrolysis temperature is 550-750° C.;

[0033] (2) The particle size of the carbon powder is between 50 and 150 μm;

[0034] (3) the activator comprises at least one of NaOH and KOH;

[0035] (4) The mass ratio of the activator to the carbon powder is (1.5-5):1, preferably (3.5-4.2):1;

[0036] (5) The activation pore-forming temperature is between 800 and 1300° C.;

[0037] (6) The protective gas A includes one or more of nitrogen and argon;

[0038] (7) The carbon source precursor is selected from at least one of synthetic resins, biomass materials and petroleum coke materials. Among them, synthetic resins include epoxy resins and / or phenolic resins, biomass materials include at least one of coconut shells, walnut shells, rice, and sugars, and petroleum coke includes petroleum asphalt and / or coal tar;

[0039] (8) The activation and pore-forming time is 5 to 10 hours.

[0040] In a possible implementation manner, commercially available porous carbon may also be directly purchased.

[0041] In a possible embodiment, S2 includes: heating the porous carbon to 300-1500° C. under protective gas B; then switching protective gas B to a mixed gas of silane gas-protective gas B, with a volume ratio of (5-35): (95-65), a gas flow rate of the mixed gas of 0.5-50 L / min, and reacting at a constant temperature for 0.5-50 h to obtain a composite material A;

[0042] Optionally, the silane gas is selected from one or more of SiH4, Si2H6, Si3H8, SiCl4, SiHCl3, Si2Cl6, SiH2Cl2, and SiH3Cl;

[0043] Optionally, the protective gas B includes one or more of nitrogen and argon;

[0044] Optionally, the porous carbon is heated to 450-650° C. under protective gas B;

[0045] Optionally, in the mixed gas of silane gas-shielding gas B, the volume ratio of the two gases is (15-30): (70-85);

[0046] Optionally, in S2, the composite material A and S x Mix evenly according to the mass ratio of (98-99.9): (0.1-2).

[0047] The molecular diameter of silane gas SiH4 is 0.4nm. As can be expected, the diameters of other silane gases are larger. Silane molecules cannot enter holes with a pore size smaller than 0.4nm and cannot be cleaved and deposited. Therefore, no silicon is deposited in holes with a pore size smaller than 0.4nm.

[0048] In a possible implementation, S2 further includes: mixing the composite material A with S x The mixture is uniformly mixed in a mass ratio of (99.9-95): (0.1-5) and then ball-milled to obtain a mixture, and then the mixture is heated to 130-180° C. under a protective gas C and reacted for 0.5-20 hours to obtain a composite material B;

[0049] Optionally, the protective gas C includes one or more of nitrogen and argon.

[0050] In a possible implementation, S3 includes: depositing and coating the product of S2 with metal oxide under heating conditions to form a coating layer on the outer surface of the porous carbon and / or the inner wall of the hollow silicon nanotube;

[0051] Optionally, the metal oxide includes one or more of Al2O3 and TiO2;

[0052] Optionally, the heating temperature is 140-160°C.

[0053] In a third aspect, the present invention provides a negative electrode sheet, comprising a current collector and an active layer disposed on at least one side of the current collector;

[0054] The active layer includes the above-mentioned silicon-carbon material or the silicon-carbon material prepared according to the above-mentioned method; the expansion of the pole piece can be reduced and the cycle of the battery can be improved.

[0055] Optionally, the active layer further comprises graphite, and the mass ratio of graphite to the silicon-carbon material is (98-50):(2-50).

[0056] In a fourth aspect, the present invention provides a secondary battery, comprising the negative electrode sheet, which reduces the expansion of silicon-carbon materials, thereby improving the cycle performance of the battery.

[0057] In some possible embodiments, the secondary battery further includes a positive electrode plate, a separator and an electrolyte.

[0058] The technical solution of the present invention has the following advantages:

[0059] 1. The silicon-carbon material of the present invention comprises porous carbon and silicon deposited in the pores of the porous carbon; the porous carbon comprises mesopores and macropores, the pore size of the mesopores is 10nm<≤50nm, and the pore size of the macropores is 50nm<≤100nm; based on the total volume of the pores on the porous carbon, the volume fraction of the mesopores is 50%~75%, and the volume fraction of the macropores is 10%~20%; the silicon deposited in the mesopores and macropores is hollow silicon nanotubes.

[0060] The silicon in the silicon-carbon material of the present invention mainly exists in the form of hollow silicon nanotubes. When lithium is embedded and expanded, space for expansion is reserved inside the hollow nanotubes. Compared with conventional silicon-carbon materials mainly composed of micropores, the overall lithium embedding expansion of the silicon-carbon material can be reduced, and the phenomenon of porous carbon skeleton breakage caused by expansion can be reduced, thereby improving the cycle performance of the battery.

[0061] 2. The porous carbon outer surface and / or the inner wall of the hollow silicon nanotube of the present invention is provided with a doping layer, and the doping layer composition includes S x, wherein x is selected from at least one of 2, 4, 6, and 8.

[0062] The doping layer components exist alone in the form of a single substance, which has a high reduction characteristic. During the charging process of the battery, they can preferentially form a uniform and high-quality SEI layer on the surface of the negative electrode, thereby improving the stability of the SEI film on the surface of the silicon-carbon material during the charging and discharging process, thereby improving the cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0063] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0064] Figure 1 This is a schematic diagram of the structure of silicon-carbon particles obtained in Example 1;

[0065] Figure 2 This is the SEM of the particle cross section of the silicon-carbon material prepared in Example 1.

[0066] Reference numerals:

[0067] 100: porous carbon, 101: hollow silicon nanotube, 102: solid silicon nanowire, 103: coating layer. DETAILED DESCRIPTION

[0068] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0069] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0070] Example 1

[0071] This embodiment provides a method for preparing a silicon-carbon material, comprising the following steps:

[0072] S1. Preparation of porous carbon: The thermosetting phenolic resin is placed in a nitrogen-protected reaction device, and the temperature is raised from room temperature to 280°C at a rate of 2°C / min and kept at this temperature for 10 hours for pretreatment, and then the temperature is raised to 700°C at a rate of 3°C / min and kept at this temperature for 4 hours for high-temperature pyrolysis; after cooling to room temperature, the mixture is crushed and passed through a 100-mesh sieve to obtain carbon powder, and the activator KOH and the carbon powder are mixed evenly at a mass ratio of 4.2:1, and the temperature is raised to 1000°C at a rate of 3°C / min, and the activation pore-forming time is 6 hours. Then the mixture is cooled to room temperature, and then washed with water, hydrochloric acid, and water in turn, and then dried to obtain the porous carbon.

[0073] S2. Deposition of nano-silicon: The obtained porous carbon is placed in a reaction equipment with a rotation speed of 1 rpm. The temperature is raised to 550°C at a rate of 2°C / min under nitrogen protection, and then maintained at 550°C for 28 hours in a 20% SiH4-80% N2 mixed atmosphere (volume ratio), wherein the gas flow rate of the mixed gas is 2.5 L / min; after cooling to room temperature in the furnace, the composite material A is obtained by crushing and grading.

[0074] Preparation of doping layer: Composite material A and S8 were mixed evenly at a mass ratio of 99:1, and then wet ball milled at a speed of 300 r / min. After drying, they were placed in a reaction device, heated to 155°C under the protection of nitrogen and maintained for 12 hours to obtain composite material B. In the composite material B prepared by the above method, a doping layer was formed on the outer surface of the porous carbon and the inner wall of the hollow silicon nanotube.

[0075] S3, surface coating: The composite material B is placed in a reactor of a rotary ALD system, and Al2O3 is deposited and coated at a temperature of 150°C. The steps include: using a 0.5s TMA (trimethylaluminum) pulse and reacting for 10s, purging with protective gas Ar for 20s to remove residual TMA and by-products, a 0.3s water vapor pulse and reacting for 10s, and purging with protective gas Ar for 20s. The above four steps are recorded as one cycle; repeat the cycle 3 times to obtain the Al2O3-coated silicon-carbon material.

[0076] The structure of the silicon-carbon material prepared in this embodiment is as follows: Figure 1 As shown, the porous carbon 100, silicon deposited on the surface of the porous carbon, and hollow silicon nanotubes 101 and solid silicon nanowires 102 deposited in the pores of the porous carbon 100, the silicon-carbon material also includes a coating layer 103 arranged on the outer surface of the porous carbon and the inner wall of the hollow silicon nanotube. The outer surface of the porous carbon and the inner wall of the hollow silicon nanotube are formed with a doping layer ( Figure 1 (not shown in the figure), the doping layer is arranged between the surface of the porous carbon 100 and the coating layer 103 and between the inner wall of the hollow silicon nanotube 101 and the coating layer 103.

[0077] Figure 2 This is a SEM of the particle cross section of the silicon-carbon material prepared in this embodiment, and there are mesopores and macropores in the material; (small pores cannot be identified by SEM).

[0078] Example 2

[0079] This embodiment provides a method for preparing a silicon-carbon material, which is basically consistent with Embodiment 1, except that, in the preparation of S1 porous carbon, the activation time is 10 hours.

[0080] Example 3

[0081] This embodiment provides a method for preparing a silicon-carbon material, which is basically consistent with Embodiment 1, except that, in the preparation of S1 porous carbon, the mass ratio of activator KOH to carbon powder is 3.5:1.

[0082] Example 4

[0083] This embodiment provides a method for preparing a silicon-carbon material, which is basically consistent with Embodiment 1, except that, during the deposition of S2 nano-silicon, the mixed atmosphere (volume ratio) of 20% SiH4-80% N2 is maintained at 650°C for 28 hours.

[0084] Example 5

[0085] This embodiment provides a method for preparing a silicon-carbon material, which is basically consistent with Embodiment 1, except that, during the deposition of S2 nano-silicon, the mixed atmosphere (volume ratio) of 20% SiH4-80% N2 is maintained at 450°C for 30 hours.

[0086] Example 6

[0087] This embodiment provides a method for preparing a silicon-carbon material, which is basically consistent with Embodiment 1, except that, during the deposition of S2 nano-silicon, the mixed atmosphere (volume ratio) of 30% SiH4-70% N2 is maintained at 650°C for 28 hours.

[0088] Example 7

[0089] This embodiment provides a method for preparing a silicon-carbon material, which is basically consistent with Embodiment 1, except that, during the deposition of S2 nano-silicon, the mixed atmosphere of 15% SiH4-85% N2 (volume ratio) is maintained at 650°C for 30 hours.

[0090] Example 8

[0091] This embodiment provides a method for preparing a silicon-carbon material, which is basically consistent with Embodiment 1, except that, during the preparation of the S2 doping layer, the mass ratio of the composite material A to S8 is 99.5:0.5.

[0092] Example 9

[0093] This embodiment provides a method for preparing a silicon-carbon material, which is basically consistent with Embodiment 1, except that, during the preparation of the S2 doping layer, the mass ratio of the composite material A to S8 is 98:2.

[0094] Example 10

[0095] This embodiment provides a method for preparing a silicon-carbon material, which is basically consistent with Embodiment 1, except that the surface coating of S3 is TiO2.

[0096] Embodiment 11

[0097] This embodiment provides a method for preparing a silicon-carbon material, which is basically consistent with Embodiment 1, except that, during the preparation of the S2 doping layer, the mass ratio of the composite material A to S8 is 90:10.

[0098] Example 12

[0099] This embodiment provides a method for preparing a silicon-carbon material, which is basically consistent with Embodiment 1, except that S2 does not undergo a doping layer preparation process, that is, the mass ratio of the composite material A to S8 is 100:0.

[0100] Comparative Example 1

[0101] This comparative example provides a method for preparing a silicon-carbon material, which is basically the same as Example 1, except that the activation time of the porous carbon is 2 hours.

[0102] Comparative Example 2

[0103] This comparative example provides a silicon-carbon composite negative electrode material, which is purchased from Lanxi Zhide New Energy Materials Co., Ltd. and has a silicon-carbon material brand number of S0332.

[0104] Test Case

[0105] (1) Specific surface area, pore size distribution and pore volume test of materials

[0106] According to GB / T 21650.2 2008, the nitrogen adsorption-desorption curves of porous carbon materials and silicon carbon materials were tested respectively, and then the specific surface area, pore size distribution and pore volume of the materials were calculated based on the BET method.

[0107] (2) Hollow silicon nanotube wall thickness test

[0108] Using a high-resolution transmission electron microscope, according to conventional sample preparation and testing methods, the silicon-carbon material was dispersed in alcohol at a concentration of 0.1 mg / mL, and then coated on a 300-mesh copper grid. After drying, the hollow silicon nanotube wall thickness test was performed. The acceleration voltage was between 80-200 kV and the beam intensity was selected between 1-10 nA; the average value of 5 points for each particle was taken as the final hollow silicon nanotube wall thickness.

[0109] (3) Average particle size Dv50 test of silicon carbon material

[0110] The volume particle size distribution curve of the silicon-carbon material was obtained by testing according to the method of GB / T 19077-2016, and the particle size corresponding to when the cumulative volume distribution percentage reached 50% was taken as the average particle size Dv50.

[0111] The test results are shown in Table 1.

[0112] Table 1

[0113]

[0114]

[0115] Preparation of secondary batteries:

[0116] Preparation of negative electrode sheet: The silicon-carbon material of each embodiment and comparative example is uniformly dispersed with graphite, binder SBR, binder PAA, conductive agent SP, conductive agent CNT, and dispersant CMC in a mass ratio of 15:80:1.5:2.5:0.9:0.04:0.06 in deionized water to obtain negative electrode slurry; the negative electrode slurry is uniformly coated on a copper foil with a thickness of 6 μm, and a negative electrode sheet is obtained after drying, rolling, slitting and other processes.

[0117] Preparation of positive electrode sheet: LiNi 0.8 Co 0.1 Mn 0.1 O2, conductive agent SP, and binder PVDF are uniformly mixed in a mass ratio of 97:1.5:1.5, and then dispersed in a solvent NMP to obtain a positive electrode slurry; the slurry is uniformly coated on the surface of the current collector aluminum foil, and the positive electrode sheet is obtained after drying, roller pressing, slitting and other processes.

[0118] Preparation of electrolyte:

[0119] Ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), and fluoroethylene carbonate (FEC) are mixed in a volume ratio of 10:20:40:20:10 to obtain a mixed solvent, 1MLiPF6 is added thereto as a main salt, and 2wt% of VC, 2wt% LiFSI, 0.5wt% DTD, 0.5wt% LiPO2F2, and 1wt% ADN are added as electrolyte additives to prepare an electrolyte.

[0120] Preparation of diaphragm:

[0121] The ceramic + PVDF coated diaphragm produced by Jiangsu Zhuogao New Materials Technology Co., Ltd. is selected as the diaphragm.

[0122] The negative electrode sheet, the separator, and the positive electrode sheet are stacked in order so that the separator is between the positive and negative electrode sheets, and then a bare battery cell is obtained by stacking the sheets; the bare battery cell is placed in an outer packaging shell, and after baking, an electrolyte is injected, and after vacuum packaging, aging, formation, capacity division and other processes, a lithium-ion soft-pack battery with a theoretical capacity of 9.0Ah is obtained.

[0123] (4) Negative electrode expansion characteristics test

[0124] In a constant temperature environment of 25℃, use a soft pack battery test fixture to fix the battery with a constant pressure of 300N, let it stand for 5 minutes, charge the divided battery to 4.25V at a rate of 1C, and charge it at a constant voltage until 0.05C is cut off. Then, the battery is disassembled in a fully charged state, and the thickness of the negative electrode sheet L1μm is measured. The thickness of the freshly made and rolled one is recorded as L0μm, and the divided capacity expansion rate is calculated according to the following formula: divided capacity expansion rate = (L1-6) / (L0-6)*100%.

[0125] In a constant temperature environment of 25℃, use a soft pack battery test fixture to fix the battery with a constant pressure of 300N, let it stand for 5 minutes, charge the battery to 4.25V at a rate of 1C, charge it at a constant voltage to 0.05C, let it stand for 5 minutes, and then discharge it to 2.5V at a rate of 1C. Repeat the above charging and discharging steps 300 times, then disassemble it in a fully charged state, and measure the thickness of the negative electrode sheet L2μm. The expansion rate of 300 cycles is calculated according to the following formula: Cycle expansion rate = (L2-6) / (L0-6)*100%. The 6 in the cycle expansion rate calculation formula is the thickness of the copper foil, in μm.

[0126] (5) Cycle performance test of secondary batteries

[0127] In a constant temperature environment of 25℃, use a soft pack battery test fixture to fix the battery with a constant pressure of 300N, let it stand for 5 minutes, charge the battery to 4.25V at a rate of 1C, charge it to 0.05C at a constant voltage, let it stand for 5 minutes, and then discharge it to 2.5V at a rate of 1C, and repeat the above charge and discharge steps for 1500 cycles. Among them, a recovery cycle with a current of 0.05C is performed after every 100 cycles: charge the battery to 4.25V at a rate of 0.05C, let it stand for 5 minutes, and then discharge it to 2.5V at a rate of 1C.

[0128] Capacity retention rate after 1500 cycles = discharge capacity after 1500 cycles / first cycle discharge capacity.

[0129] Observe the capacity decay curve of the battery during the cycle process to see if there is an accelerated capacity decay phenomenon in the later stage of the cycle. If so, it is recorded as capacity diving, and if not, it is recorded as normal.

[0130] The test results are shown in Table 1-Table 2.

[0131] Table 2

[0132]

[0133] It can be seen from Examples 1 to 12 and Comparative Examples 1 to 2 in Table 2 that the negative electrode capacity expansion rate and cycle expansion rate of the secondary battery made of the silicon-carbon material of the present invention are significantly reduced compared to those of the secondary battery made of the existing silicon-carbon material, and the battery has a higher cycle capacity retention rate, does not drop in the middle and late stages of the cycle, and has better cycle performance.

[0134] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A silicon-carbon material, characterized in that: comprising porous carbon and silicon deposited in the pores of the porous carbon; The porous carbon includes mesopores and macropores, with the pore size of the mesopores being 10nm<≤50nm, and the pore size of the macropores being 50nm<≤100nm; Based on the total volume of the pores on the porous carbon, the volume fraction of the mesopores is 50% to 75%, and the volume fraction of the macropores is 10% to 20%; The silicon deposited in the mesopores and macropores is hollow silicon nanotubes.

2. The silicon-carbon material according to claim 1, characterized in that: The wall thickness of the hollow silicon nanotube is 0.6-5 nm, preferably 0.6-3 nm, and more preferably 1.8-2.4 nm.

3. The silicon-carbon material according to claim 1, characterized in that: At least one of the following conditions is met: (1) Based on the total volume of pores on the porous carbon, the volume fraction of the mesopores is 58% to 70%; (2) The porous carbon further comprises small pores with a pore diameter of ≤10 nm, and the volume fraction of the small pores is ≤40% based on the total volume of the pores on the porous carbon; The silicon deposited in the small holes is solid silicon nanowires and / or hollow silicon nanotubes.

4. The silicon-carbon material according to claim 1, characterized in that: The silicon-carbon material further comprises a coating layer disposed on the outer surface of the porous carbon and / or the inner wall of the hollow silicon nanotube; Optionally, the coating layer is selected from at least one of a carbon coating layer, a polymer coating layer, a metal oxide coating layer and an organic-inorganic composite coating layer.

5. The silicon-carbon material according to claim 4, characterized in that: A doping layer is provided on the outer surface of the porous carbon and / or the inner wall of the hollow silicon nanotube; Optionally, the composition of the doping layer includes S x , wherein x is selected from at least one of 2, 4, 6, and 8; Optionally, the doping layer is disposed between the porous carbon and the coating layer, and / or the doping layer is disposed between the inner wall of the hollow silicon nanotube and the coating layer; Optionally, the mass of the doping layer accounts for 0.1% to 5%, preferably 0.5% to 2%, of the sum of the mass of the porous carbon, silicon and the doping layer.

6. A method for preparing the silicon-carbon material according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. Obtaining porous carbon: pyrolyzing a carbon source precursor under a protective gas A, crushing and classifying the carbon powder, mixing the carbon powder with an activator, and then heating the mixture to activate and form pores, thereby obtaining the porous carbon; The activation pore-forming time is 5 to 24 hours; S2, depositing silicon in the pores of porous carbon; S3. Prepare a coating layer.

7. The method for preparing the silicon-carbon material according to claim 6, characterized in that: S1 satisfies at least one of the following conditions: (1) The pyrolysis temperature is 550-750° C.; (2) The particle size of the carbon powder is between 50 and 150 μm; (3) the activator comprises at least one of NaOH and KOH; (4) The mass ratio of the activator to the carbon powder is (1.5-5):1, preferably (3.5-4.2):1; (5) The activation pore-forming temperature is between 800 and 1300° C.; (6) The protective gas A includes one or more of nitrogen and argon; (7) The carbon source precursor is selected from at least one of synthetic resins, biomass materials and petroleum coke materials; (8) The activation and pore-forming time is 5 to 10 hours.

8. The method for preparing the silicon-carbon material according to claim 6, characterized in that: S2 includes: The porous carbon is heated to 300-1500° C. under protective gas B; then the protective gas B is switched to a mixed gas of silane gas-protective gas B, with a volume ratio of (5-35): (95-65), a gas flow rate of the mixed gas of 0.5-50 L / min, and the reaction is carried out at a constant temperature for 0.5-50 hours to obtain a composite material A; Optionally, the silane gas is selected from one or more of SiH4, Si2H6, Si3H8, SiCl4, SiHCl3, Si2Cl6, SiH2Cl2, and SiH3Cl; Optionally, the protective gas B includes one or more of nitrogen and argon; Optionally, S2 further comprises: mixing the composite material A with S x The mixture is uniformly mixed in a mass ratio of (99.9-95): (0.1-5) and then ball-milled to obtain a mixture, and then the mixture is heated to 130-180° C. under a protective gas C and reacted for 0.5-20 hours to obtain a composite material B; Optionally, the protective gas C includes one or more of nitrogen and argon; Optionally, the porous carbon is heated to 450-650° C. under protective gas B; Optionally, in the mixed gas of silane gas-shielding gas B, the volume ratio of the two gases is (15-30): (70-85); Optionally, in S2, the composite material A and S x Mix evenly according to the mass ratio of (98-99.9): (0.1-2).

9. A negative electrode plate, characterized in that: comprising a current collector and an active layer disposed on at least one side of the current collector; The active layer comprises the silicon-carbon material according to any one of claims 1 to 6 or the silicon-carbon material prepared according to the method of claim 7 or 8; Optionally, the active layer further comprises graphite, and the mass ratio of graphite to the silicon-carbon material is (98-50):(2-50).

10. A secondary battery, characterized in that: Including the negative electrode sheet as described in claim 9.

Citation Information

Cited By

  • Negative electrode material and preparation method thereof, secondary battery and electronic device

    CN119965252A

  • Negative electrode material, method for preparing the same, secondary battery, and electronic device

    CN119965252B

  • Silicon-carbon negative electrode material, preparation method thereof and secondary battery

    CN120690838A